2021
DOI: 10.1016/j.jtho.2021.01.299
|View full text |Cite
|
Sign up to set email alerts
|

OA07.08 HUDSON: An Open-Label, Multi-Drug, Biomarker-Directed, Phase II Platform Study in Patients with NSCLC, who Progressed on Anti-PD(L)1 Therapy

Abstract: IFN-g-induced expression of PD-L1 was impaired in LKB1-loss and LKB1-mutant groups (A549-LV-control and A549-LV-KD), and the key vulnerability lies in decreased phosphorylated STAT1 expression and its transcriptional activity. Mass spectrometry (MS) and subsequent CO-IP showed that LKB1 interacted with PARP1 and decreased the catalytic activity of PARP1. Upon IFNg simulation, PARP1 poly (ADPribosyl)ated STAT1 and subsequently inhibited STAT1 phosphorylation, which thereby impaired PD-L1 expression in LKB1 defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Various studies of anti‐CD73 monoclonal antibodies in combination with PD‐(L)1 inhibitors are ongoing in NSCLC (Table 3). These include the phase 2 HUDSON trial, which includes an arm investigating the anti‐CD73 antibody oleclumab in combination with durvalumab in patients with locally advanced and/or metastatic NSCLC who progressed after prior PD‐(L)1 inhibitor 123 . This combination improved ORR and PFS versus durvalumab alone after concurrent chemoradiotherapy in unresectable stage III NSCLC in the phase 2 COAST trial, with an ORR of 38.3% versus 25.4%, respectively, for oleclumab plus durvalumab versus durvalumab alone 124 .…”
Section: Strategies For Enhancing Responses and Countering Resistance...mentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies of anti‐CD73 monoclonal antibodies in combination with PD‐(L)1 inhibitors are ongoing in NSCLC (Table 3). These include the phase 2 HUDSON trial, which includes an arm investigating the anti‐CD73 antibody oleclumab in combination with durvalumab in patients with locally advanced and/or metastatic NSCLC who progressed after prior PD‐(L)1 inhibitor 123 . This combination improved ORR and PFS versus durvalumab alone after concurrent chemoradiotherapy in unresectable stage III NSCLC in the phase 2 COAST trial, with an ORR of 38.3% versus 25.4%, respectively, for oleclumab plus durvalumab versus durvalumab alone 124 .…”
Section: Strategies For Enhancing Responses and Countering Resistance...mentioning
confidence: 99%
“…Median PFS was not reached for the combination versus 6.3 months for durvalumab alone 124 . However, preliminary results of the HUDSON trial appear disappointing, with no responses reported in an early 2020 data‐cut from either the biomarker‐matched cohort (ORR, 0%; 6‐month OS, 79.9%; 6‐month PFS, 8.3%) or the biomarker nonmatched cohort (ORR, 0%; 6‐month OS and PFS, not calculable [primary resistance]; ORR, 0%; 6‐month OS, 64.4%; 6‐month PFS, 26.1% [acquired resistance]) 123 …”
Section: Strategies For Enhancing Responses and Countering Resistance...mentioning
confidence: 99%
“…12 13 In addition, melanoma and non-small cell lung cancer patients who were previously treated with anti-PD1 agents showed favorable responses in a currently ongoing phase II clinical trial. 14 15 Here, we report the first phase II trial of ceralasertib plus durvalumab (ceralasertib +durvalumab), an anti-PD-L1 antibody, for AGC treatment. We demonstrated the safety, tolerability, and clinical activity of this combination in patients with chemorefractory AGC.…”
Section: What This Study Addsmentioning
confidence: 99%
“… 12 13 In addition, melanoma and non-small cell lung cancer patients who were previously treated with anti-PD1 agents showed favorable responses in a currently ongoing phase II clinical trial. 14 15 …”
Section: Introductionmentioning
confidence: 99%
“…PALB2 has been explored in the field of chemotherapy, and the presence of PALB2 mutation has been reported to be correlated with improved clinical outcomes in non-small cell lung cancer (NSCLC) treated with platinum-based chemotherapy (10). None of the previously reported studies of the correlation between the DDR gene and lung cancer immunotherapy has independently verified PALB2 (11)(12)(13). Therefore, it is necessary to analyze the PALB2 mutation characteristics in the Chinese NSCLC population and demonstrate whether PALB2 mutation is associated with immunotherapy responses.…”
Section: Introductionmentioning
confidence: 99%